Design of Goods Inventory Information System Using Visual Basic .Net (Case Study: CV. Barokah Medan) - Pardede, Ilda Aprisya; Marbun, Nasib (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
CV Barokah Medan is a company engaged in the distributor of beverage powder. This company was founded in 2019. Currently, the inventory process at CV Barokah Medan is still carried out conventionally, namely by using ledger records and Microsoft Excel tools. By using the current system, it takes a lot of time to search for goods because of the large number of items, then the problem that occurs is that there is data redundancy and notebooks and inventory data files are damaged or lost so that the checking process takes a long time and is mistaken in the data recording process. Efforts to overcome these problems in this study the authors are interested in creating an inventory information system using the visual basic .net programming language at CV. Barokah Medan. Visual basic .net is visual basic that is re-engineered for use on the .NET platform so that applications created using visual basic .NET can run on computer systems supported by the windows operating system. The results of this study indicate that the proposed inventory information system at CV. Barokah Medan can be used to store and process data in the warehouse, namely item data reports, supplier data reports, and inventory reports per day, per month and per year. So that it can support the CV. Barokah Medan to achieve higher productivity, and save costs, energy, and time in collecting, retrieving and managing inventory data, as well as displaying information data quickly and accurately.